SPECIFIC FEATURES OF LABOR RESOURCES IN THE TOURISM SECTOR - Ibotova Mohinur Toshtemir qizi (Modern American Journals, 2025)
This article analyzes the economic and social characteristics of labor resources in the tourism sector, their effective management, and the role of the human factor in industry development. The study reveals specific features of tourism labor such as the service-oriented nature of work, seasonality, emotional labor, and teamwork. Additionally, the article discusses current challenges and priority directions for developing labor resources in Uzbekistan’s tourism industry.
Keywords: Tourism, labor resources, human factor, seasonality, service culture, personnel policy, sustainable development.